Gonadotropin-releasing hormone antagonists versus standard androgen suppression therapy for advanced prostate cancer A systematic review with meta-analysis. Issue 11 (13th November 2015) - Kunath, Frank; Borgmann, Hendrik; Blümle, Anette; Keck, Bastian; Wullich, Bernd; Schmucker, Christine; Sikic, Danijel; Roelle, Catharina; Schmidt, Stefanie; Wahba, Amr; Meerpohl, Joerg J
Abstract : Objectives: To evaluate efficacy and safety of gonadotropin-releasing hormone (GnRH) antagonists compared to standard androgen suppression therapy for advanced prostate cancer. Setting: The international review team included methodologists of the German Cochrane Centre and clinical experts. Participants: We searched CENTRAL, MEDLINE, Web of Science, EMBASE, trial registries and conference books for randomised controlled trials (RCT) for effectiveness data analysis, and randomised or non-randomised controlled studies (non-RCT) for safety data analysis (March 2015). Two authors independently screened identified articles, extracted data, evaluated risk of bias and rated quality of evidence according to GRADE. Results: 13 studies (10 RCTs, 3 non-RCTs) were included. No study reported cancer-specific survival or clinical progression. There were no differences in overall mortality (RR 1.35, 95% CI 0.63 to 2.93), treatment failure (RR 0.91, 95% CI 0.70 to 1.17) or prostate-specific antigen progression (RR 0.83, 95% CI 0.64 to 1.06). While there was no difference in quality of life related to urinary symptoms, improved quality of life regarding prostate symptoms, measured with the International Prostate Symptom Score (IPSS), with the use of GnRH antagonists compared with the use of standard androgen suppression therapy (mean score difference −0.40, 95% CI −0.94 to 0.14, and −1.84, 95% CI −3.00 to −0.69, respectively) was found. Quality of evidence for all assessed outcomes was rated low according to GRADE. The risk for injection-site events was increased, but cardiovascular events may occur less often by using GnRH antagonist. Available evidence is hampered by risk of bias, selective reporting and limited follow-up. Conclusions: There is currently insufficient evidence to make firm conclusive statements on the efficacy of GnRH antagonist compared to standard androgen suppression therapy for advanced prostate cancer. There is need for further high-quality research on GnRH antagonists with long-term follow-up. Trial registration number: CRD42012002751.